Procedural control and the proper balance between public and private interests in defamation claims - Hyde, Richard (Taylor & Francis, 2014)
Claims in defamation involve courts in balancing of a number of interests. The Claimant’s interest in their reputation must be balanced with the Defendant’s interest in free expression. The Court’s interest in fair, efficient and proportionate adjudication must be balanced against the Claimant’s interest in vindicating their reputation. Much of the literature examining this balance has focused on the substantive law. This article seeks to consider how these interests have been balanced through procedural control mechanisms, such as summary judgment and strike out. In particular, the development of the court’s ability to strike out a claim as an abuse of process is been considered. It is argued that the ability to strike out in such cases performs an important role, but should not be used to prevent reputational vindication where this is worthwhile. Further, it is argued that whilst substantive and procedural changes may reduce the need for strike out, the courts should not remove this important tool from their toolbox.